2011
DOI: 10.1159/000330120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rearing Temperatures during Embryonic Development on the Phenotypic Sex in Zebrafish <i>(Danio rerio)</i>

Abstract: In zebrafish, Danio rerio, a polygenic pattern of sex determination or a female heterogamety with possible influences of environmental factors is assumed. The present study focuses on the effects of an elevated water temperature (35°C) during the embryonic development on sex determination in zebrafish. Eggs derived from 3 golden females were fertilized by the same mitotic gynogenetic male and exposed to a water temperature of 35°C, applied from 5 to 10 h post fertilization (hpf), from 5 to 24 hpf, and from 5 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
59
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 69 publications
7
59
1
Order By: Relevance
“…In domesticated zebrafish, the effects of elevated temperature have been studied after exposure periods concerning embryos (35), juveniles (36,37), or development until adults (38,39). In agreement with the general pattern in fish (18), elevated temperatures result in a higher number of males, although, surprisingly, one study reported more females (40).…”
mentioning
confidence: 77%
“…In domesticated zebrafish, the effects of elevated temperature have been studied after exposure periods concerning embryos (35), juveniles (36,37), or development until adults (38,39). In agreement with the general pattern in fish (18), elevated temperatures result in a higher number of males, although, surprisingly, one study reported more females (40).…”
mentioning
confidence: 77%
“…Answers likely lie in environmental factors and background genetic features that affect the strength of a meiotic oocyte-derived pro-female signal that inhibits oocyte apoptosis, probably by maintaining aromatase production (Slanchev et al 2005;Houwing et al 2007;Wang et al 2007;Siegfried and Nusslein-Volhard 2008;Rodriguez-Mari et al 2010Rodríguez-Marí and Postlethwait 2011;Pradhan et al 2012;Dranow et al 2013). In general, harsh conditions, including high density and poor nutrition, tend to promote male development (Walker-Durchanek 1980;Pelegri and Schulte-Merker 1999;Shang et al 2006;Lawrence et al 2008;Abozaid et al 2011Abozaid et al , 2012Liew et al 2012;Villamizar et al 2012). These harsh factors may act to decrease the pro-female signal by depressing the pool of meiotic oocytes, either by inhibiting primary germ-cell proliferation or entry into meiosis or by promoting oocyte apoptosis.…”
Section: Domesticated Zebrafish Strains Lack a Single Strong Sexlinkementioning
confidence: 99%
“…As expected from the hypothesis that oocyte death is a major feature of zebrafish sex determination, harsh environmental conditions tend to shift sex ratios in favor of males; such factors include gamma rays, hypoxia, high density, high temperature, altered thermocycles, and poor nutrition (Walker-Durchanek 1980;Shang et al 2006;Lawrence et al 2008;Abozaid et al 2011Abozaid et al , 2012Liew et al 2012;Villamizar et al 2012). Zebrafish does not, however, have a typical environmental sex-determination (ESD) mechanism like some sauropsids for which temperature is a cue (Charnier 1966;Lang and Andrews 1994;Merchant-Larios and Diaz-Hernandez 2013;Mork et al 2014).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Morphological differences in the chromosomes of the 2 sexes have not been identified by classical karyotyping, implicating poly genetic or environmental signals in sex determination [Amores and Postlethwait, 1999;Sola and Gornung, 2001;Traut and Winking, 2001;Wallace and Wallace, 2003]. With regard to previous studies, sex determination in zebrafish might be controlled by a combination of genetic and environmental factors [Siegfried and Nüsslein-Volhard, 2008;Orban et al, 2009;Abozaid et al, 2011;Bradley et al, 2011;López-Olmeda and Sánchez-Váz quez, 2011]. Tong et al [2010] assumed that the phenotypic sex of zebrafish is determined by female-dominant genetic factors (ZW).…”
mentioning
confidence: 99%